Association of clinical symptoms and neurocognitive performance in bipolar disorder: a longitudinal study - Chaves, Olga C (2011)
OBJECTIVE: Despite evidence that individuals with bipolar disorder have neurocognitive impairment that persists during euthymia, the impact of changes in affective symptoms on cognitive function has not been well established. Here, we sought to determine whether specific neurocognitive functions are sensitive to mood changes in individuals with bipolar disorder assessed three months apart without changes in treatment regimen. METHODS: A total of 29 individuals with DSM-IV bipolar disorder and 30 healthy controls participated in the study. All participants received a comprehensive neuropsychological assessment and ratings of depressive [Hamilton Depression Rating Scale (HAMD)] and manic [Young Mania Rating Scale (YMRS)] symptoms at baseline and follow-up. Changes in symptoms over time were calculated and were examined in relation to changes in neurocognitive performance. RESULTS: At baseline, clinically stable but symptomatic patients were impaired on measures of speed of processing and attention. Over the three-month follow-up period, HAMD scores changed by 6 points on average [range: −10 to +18] and YMRS scores changed by 5.31 points on average [range −11 to +15]. Changes in depressive symptoms were correlated with poorer verbal fluency, while no relationship between manic symptoms and neuropsychological performance was detected. CONCLUSIONS: Individuals with bipolar disorder showed consistent impairment on speed of processing and attention over time, despite significant changes in mood.